2023
DOI: 10.1021/acs.chemrev.2c00399
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic, Carbon-Reinforced Soil as a Living Engineered Material

Abstract: In recent years, the simple synthesis of artificial humic substances (A-HS) by alkaline hydrothermal processing of waste biomass was described. This A-HS was shown to support water and mineral binding, to change soil structure, to avoid fertilizer mineralization, and to support plant growth. Many of the observed macroscopic effects could, however, not be directly related to the minute amounts of A-HS which have been added, and an A-HS stimulated microbiome was found to be the key for understanding. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…In addition to nonrenewable geochemical sources of humic materials, suggested approach can be implemented for humic acids extracted from recycled biomass (compost, worms-compost, biochar, biorefinery residues, etc.) or artificial HS that can offer a wider range of promising bioactive components. , The potential applications of narrow fractions of HS refer both to biomedical technologies and to novel agricultural technologies, in particular, humics-based bioctimulators and nanofertilizers. , Further research in the field of high-resolution separation of HS materials may bring substantial advances in separation, not only by the chemotypes but by similar chemical scaffolds, which may eventually enable isolation of individual bioactive compounds from the humic supramolecular systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nonrenewable geochemical sources of humic materials, suggested approach can be implemented for humic acids extracted from recycled biomass (compost, worms-compost, biochar, biorefinery residues, etc.) or artificial HS that can offer a wider range of promising bioactive components. , The potential applications of narrow fractions of HS refer both to biomedical technologies and to novel agricultural technologies, in particular, humics-based bioctimulators and nanofertilizers. , Further research in the field of high-resolution separation of HS materials may bring substantial advances in separation, not only by the chemotypes but by similar chemical scaffolds, which may eventually enable isolation of individual bioactive compounds from the humic supramolecular systems.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial humic acid (A-HA), an emerging EOC derived from biological by-products or waste, has a carbon-negative property [ 13 , 14 ]. Our previous research has identified A-HA as a facilitator for the establishment of interactive microbial systems along mineral particle interfaces and plays an important role in maintaining soil ecosystem services [ 15 , 16 ]. A-HS has been proved to change soil structure, support water and mineral binding, avoid fertilizer mineralization, and furthermore support plant growth [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Humic Substances (AHS) are emerging as a sustainable and versatile tool to address the challenges of modern agriculture (Yang and Antonietti, 2020;Yang et al, 2023). These substances, synthesized through the hydrothermal conversion of biomass, mimic the properties and functionalities of natural HS.…”
Section: Introductionmentioning
confidence: 99%